The Impact of Temperature Oscillations and Heat Transfer Conditions in Thick-Walled Elbows and Tubes on the Local Stress-Strain Behaviour During the Fast Start-Up of Power Boilers - OKRAJNI, Jerzy; WACŁAWIAK, Krzysztof (Engineering Transactions, 2019)
The paper presents results of tests designed for predicting the behaviour of components subjected to variable temperature and mechanical loading conditions. Elbows and tubes, as examples of components widely used in power plant pipelines, have been examined. This analysis includes a description of model characteristics, the operating parameters of devices under industrial conditions, and the results of computational modelling (FEM).